The Influence of Translation Politics in the Formation of Canon. The Example of Judita Vaičiūnaitė - Bernotienė, Gintarė (Colloquia, 2016)
The author of this article explores how, during the 1960s–1980s, certain actions and decisions within the literary patronage system determined which Lithuanian authors were incorporated into the Soviet Lithuanian literary canon. The article focuses on the turbulent thirty-year history of Judita Vaičiūnaitė’s recognition as a Lithuanian literary classic and the complex and ambiguous conditions of the dissemination of her writing. These points in turn reveal the significant stages of a more general process – the formation of the Lithuanian literary canon during the Soviet period. During the Soviet era, translation of an author’s work into Russian was a mandatory step in the broader dissemination of his or her work (in particular in terms of foreign readers). The author of the article treats quantitative indicators related to selection of works for translation as the criteria which most reliably indicated an author’s suitability for inclusion in the emerging Soviet literary canon and the actual position of a writer within the literary hierarchy of the time. The new archival documents examined reveal at least in part the process for selecting authors and works. Other factors regulating Soviet translation policy did not survive – they were undocumented and depended on extra-literary factors. In particular, the stages of the official literary patronage involved assessment of the ideological suitability of a work and took into account the author’s longterm loyalty, both of which were rewarded by greater possibilities for dissemination.